The Influence of AI Coding and Technology Tools on Human Resource Readiness Through Digital Literacy - Wulan Setyorini; K Kadeni; Muhammad Anasrulloh; Yepi Sedya Purwananti (CV. Media Digital Publikasi Indonesia, 2025)
The era of Society 5.0 demands the integration of technology and character building in education to prepare superior human resources (HR). However, preliminary observations at public elementary schools in Rejotangan District reveal a gap between policy and reality, characterized by low digital literacy and limited availability of AI-based learning tools. This study aims to analyze the influence of AI Coding-based learning implementation and the availability of technological devices on the readiness of intelligent and competitive HR, mediated by students' digital literacy in science and social studies (SASS). This research employs a quantitative approach with an associative design. The population comprises 319 Grade 5 students, with a sample of 178 students determined using the Slovin formula and proportional stratified random sampling. Data analysis utilizes Structural Equation Modeling (SEM-PLS). The findings indicate that both AI coding learning and device availability significantly influence HR readiness through digital literacy as a mediator. This research provides a model for integrating AI coding in elementary education.